(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Estimation of accurate Gestational Age (GA) is essential for antenatal care. There are different methods of estimating GA. Among them first day of Last Normal Menstrual Period (LNMP) is a common if the menstrual cycle is regular. In many countries, it was reported that Placental Thickness (PT) can be used as an alternative ultrasonographic parameter in these regards. The present study was aimed to evaluate the correlation of PT with other traditional ultrasonographic fetal biometrics to estimate GA. To measure and evaluate the placental thickness for the estimation of gestational age by ultrasonography in uncomplicated pregnant women of Chattogram, Bangladesh. Materials and methods: This cross-sectional obser- vational study was conducted among 112 uncomplicated pregnant women from 11 th to 40 th week of gestation, living in Chattogram, Bangladesh. The participants of the study were selected who had no medical complications and attended Radiology and Imaging Department of, Chittagong Medical College Hospital (CMCH) and Islami Bank Hospital Agrabad, Chattogram, according to enrollment criteria. The study subjects were divided into three groups, 11 th -13 th , 14 th – 26 th and 27 th – 40 th week. Results: In this study, the age of the respondents ranged from 18-41. In the present study PT, was observed to increase gradually as Gestational Age (GA) advances. The mean PT was 14.20±3.01 mm in 12 th week and 41.67±2.33 mm in 38 th week of gestation. Scatter diagram by pearson’s correlation test showed significant positive correlation of PT with GA in 11 th -13 th week as (r=0.61, p<0.05), 14 th -26 th week as (r=0.43, p<0.05) and in 27 - 40 th week as (r=0.29, p<0.05). Conclusion: The observations of this study showed that placental thickness was seen to increase gradually as gestational age advances. Present study demonstrated that placental thickness can be used as an ultrasonographic biometric parameter for the estimation of gestational age. JCMCTA 2025 ; 36 (1) : 71-75